A Framework for Successful Crowdfunding Campaigns: Insights from Social Media (A Systematic Review) - Saeideh Sadat Alavi; Mohammad Ghadamyari; Tahmoores Sohrabi (Journal of Asset Management and Financing)
Crowdfunding campaigns on social media have emerged as a powerful tool for entrepreneurs seeking to secure capital and mobilize support for their ventures. However, the success of these campaigns is often uncertain, and a comprehensive framework to guide practitioners in creating effective campaigns is currently lacking. The primary objective of this research is to develop a framework for successful crowdfunding campaigns on social media through a systematic review of the literature. A qualitative systematic literature review methodology was employed. Initially, 1,330 studies were screened, and after multiple stages of filtering, 29 studies were selected for in-depth analysis. The findings yield a framework that encompasses the components of successful social media crowdfunding campaigns (including project goals, brand awareness, and fundraising amounts), factors influencing campaign success (such as project characteristics, entrepreneur attributes, campaign strategy, social media activity, and psychological factors), the consequences of successful campaigns (including financial, social, and network outcomes), and intervening factors (such as platform characteristics and time constraints). This framework serves as a valuable guide for entrepreneurs, platform providers, and policymakers in formulating effective strategies to enhance the success of crowdfunding initiatives.Keywords: Crowdfunding, Social Media, Crowdfunding Success, Entrepreneurship, Systematic Literature Review. IntroductionCrowdfunding has emerged as a popular and innovative method for financing projects and businesses, enabling individuals to contribute small amounts of money to transform ambitious ideas into reality. Various online platforms facilitate crowdfunding campaigns, during which projects are showcased for a specific duration, with their success or failure determined by the amount of funds raised. Social media platforms play a pivotal role in the success of these campaigns, serving as powerful tools for promoting and sharing projects and allowing individuals to reach their target audiences effectively. Despite the significance of this topic, comprehensive research on the factors influencing the success of crowdfunding campaigns on social media remains limited. The primary objective of this study is to present a comprehensive model for predicting the success of crowdfunding campaigns on social media. This study's significance lies in its potential to help individuals and organizations design and implement more successful crowdfunding campaigns by offering a robust predictive framework. Furthermore, this research contributes to advancing knowledge in the field of crowdfunding and elucidates the role of social media in this context. In this study, a thorough review of the existing literature informs the development of a comprehensive model for the success of crowdfunding campaigns on social media. This model can serve as a valuable tool for researchers, entrepreneurs, and investors engaged in this field.Materials & MethodsThis study employed a qualitative approach through a systematic literature review (SLR) guided by the established seven-step method outlined in the Cochrane Handbook for Systematic Reviews of Interventions (Higgins & Green, 2008). The process included: (1) formulating a focused research question; (2) determining clear inclusion criteria; (3) conducting a comprehensive search for relevant studies; (4) rigorously selecting studies based on pre-defined criteria; (5) critically appraising the methodological quality of included studies; (6) systematically extracting relevant data; and (7) synthesizing and presenting the findings. A comprehensive search strategy was implemented across a range of reputable scientific databases, including domestic databases such as Noormags, SID, ensani.ir, and Magiran to capture relevant research in the local context, along with international databases such as ScienceDirect, Springer, Wiley, Sage, Emerald, and Taylor & Francis to ensure a broader search. The search encompassed publications from 2000 to 2024 and resulted in an initial collection of 1,330 studies related to crowdfunding campaigns on social media. Following a rigorous screening process based on pre-defined selection criteria—relevance to the research topic, methodological quality, and clarity of findings—the final sample for analysis comprised 29 studies. FindingsThis research aimed to develop a comprehensive framework for the success of crowdfunding campaigns on social media. Through a systematic review of the literature, it was determined that multiple factors influence the success of a crowdfunding campaign. These factors include project characteristics, the entrepreneur's attributes and abilities, campaign strategy, social media activity and interactions, social network indicators, psychological factors, platform features, and moderating variables such as time constraints and platform characteristics. Campaign success can be measured by various dimensions, including the total amount of funds raised, increased brand awareness, and the achievement of specific project goals. The research delved into the influence of various factors on campaign success. These factors encompass inherent project characteristics, the entrepreneur's personal attributes and abilities, the strategies implemented during the campaign, interactions occurring on social media, and psychological factors that impact investor decision-making. Moreover, this research explored the potential consequences of successful crowdfunding campaigns. These consequences include financial benefits, strengthened social relationships, and expanded professional networks. In conclusion, the findings of this research indicate that the success of crowdfunding campaigns on social media is a complex interplay of various factors. By gaining a deeper understanding of these factors, a robust framework can be developed to design and implement more effective crowdfunding campaigns. Discussion of Results & ConclusionThis study aimed to develop a comprehensive framework for the success of crowdfunding campaigns on social media. Through a systematic review of the literature, it was found that multiple factors influence the success of these campaigns. Key factors include project characteristics, the entrepreneur's attributes and abilities, campaign strategy, social media activity and interactions, social network indicators, psychological factors, platform features, and moderating variables such as time constraints. Campaign success can be measured across various dimensions, including the total amount of funds raised, increased brand awareness, and the achievement of specific project goals. The study examined the impact of these factors on campaign success, highlighting the importance of inherent project characteristics, the entrepreneur's personal attributes, the strategies employed during the campaign, social media interactions, and psychological factors that affect investor decision-making. Additionally, the study explored the potential consequences of successful crowdfunding campaigns, which include financial benefits, strengthened social relationships, and expanded professional networks. In conclusion, the findings indicate that the success of crowdfunding campaigns on social media is a complex interplay of various factors. By gaining a deeper understanding of these elements, a robust framework can be developed to design and implement more effective crowdfunding campaigns.